Eight Areas of Competency in Decision Making for Sustainability in Metro Food Systems - John D. WARBACH; Christine GEITH; Andrea SEXTON; Tessa KANEENE (Transylvanian Review of Administrative Sciences, 2012)
Michigan State University (MSU) held a focus group in Detroit, Michigan, USA in 2012 with members of the urban agriculture movement. The session included business persons involved in growing and selling food, members of the health system, community group members and city government. The purpose was to identify the full range of sectors of society involved in the food system, to identify the perceptions of the food system among the city population, test eight sustainability competency areas developed by MSU faculty as concepts and as they related to urban food systems, and to discover what kinds of decision support tools were needed to foster sustainable food systems in Detroit. The focus group session was video and audio recorded, the tapes transcribed and coded to identify common themes and responses to the competency area concepts. The competency areas presented were: ecological integrity, community well-being/social justice, economic vitality, aesthetic quality, civic responsibility, systems interdependence, critical thinking, and personal growth. Participants indicated that they considered sustainability a value that people in urban agriculture shared, but that people struggled with how to move forward toward sustainability. Focus group participants were able to identify some aspect of each of the eight competency areas that they perceived people in urban agriculture, and the broader city resident population already recognized, or engaged in without recognizing that they were doing something that could lead to more sustainable outcomes. However, participants perceived that a sustainable metropolitan food system remains a somewhat elusive goal to achieve for people engaged in pursuing urban agriculture in Detroit due to a negative perception they expressed that many of the city’s population holds for growing food in the city, and in general for goods produced in the city. Information gained from the focus group and subsequent focus groups with members of the different urban agriculture sectors will be used to help develop university and partner organization education programs, to identify other research needs, and to help people developing school and other youth education programs in sustainability.